Genotypic Variation in the pol Gene of HIV Type 1 in an Antiretroviral Treatment-Naive Population in Rural Southwestern Uganda - Gale, Catherine V.; Yirrell, David L.; Campbell, Eileen; Kaleebu, Pontiano (AIDS Research & Human Retroviruses, 2006)
The majority of studies of HIV-1 drug resistance have involved subtype B viruses. Here we have characterized subtype distribution and determined the levels of polymorphism at protease (PR) and reverse transcriptase (RT) drug resistance positions, in antiretroviral treatment-naive HIV-positive Ugandan patients. We have also investigated codon usage variability at these positions and assessed intersubtype recombination within the polgene. The study population consisted of 187 patients, from a cohort established by the UK Medical Research Council Programme on AIDS in Uganda in 1990. Results indicate that 28.3% of patients were infected with subtype A (n 53), 64.2% subtype D (n 120), 6.4% A/D recombinant (n 12), and 1.1% subtype C (n 2). Variation in amino acid usage at drug resistance-associated positions was minimal between the two main subtypes (A and D) in RT, but there was appreciable variation in PR. Codon usage, however, was considerably more variable between subtypes A and D in both PR and RT. Thus, while no natural high-level resistance to antiretroviral therapy was detected in this cohort, subtypes A and D may possess different genetic barriers to be overcome in order to achieve resistance. With the increasing introduction of antiretroviral therapy into Africa, such information will be vital in our understanding and evaluation of the development of drug resistance as it occurs, and how to interpret resistance data the type of which has rarely previously been seen. This analysis also significantly increases the number of Ugandan PR and RT sequences characterized to date.